Dear colleagues and readers of our journal (Condensed Matter Physics, 2013)
Our journal will turn 20 this year and we are very grateful for your support during all these years.
Our impact factor was 0.811 last year and we hope to progress in this respect. We cordially invite you
to submit manuscripts covering research in various areas of Condensed and Soft Matter Physics. Brief
reports and review papers are especially welcome.